(untitled) (Sebha University Conference Proceedings, 2025)
This study demonstrates the application of the OPNET simulation tool to assess VoIP over MPLS networks utilizing the RSVP protocol as a QoS mechanism, with SIP or H.323 serving as signaling protocols for establishing VoIP conversations over the Internet. The findings indicated that H.323 with RSVP over MPLS networks yielded lower end-to-end delay compared to the SIP protocol, rendering it an optimal choice for signaling in VoIP over MPLS networks where minimal end-to-end delay is essential. Conversely, SIP demonstrated the least delay jitter and minimal call setup time.